Reducing variation in hospital mortality for alcohol‐related liver disease in North West England. Issue 1 (22nd May 2020) - Kallis, Constantinos; Dixon, Pete; Silberberg, Benjamin; Affarah, Lynn; Shawihdi, Mustafa; Grainger, Ruth; Prospero, Nancy; Pearson, Mike; Marson, Anthony; Ramakrishnan, Subramanian; Richardson, Paul; Hood, Steve; et al.
Summary: Background: Variations in emergency care quality for alcohol‐related liver disease (ARLD) have been highlighted. Aim: To determine whether introduction of a regional quality improvement (QI) programme was associated with a reduction in potentially avoidable inpatient mortality. Method: Retrospective observational cohort study using hospital administrative data spanning a 1‐year period before (2014/2015) and 3 years after a QI initiative at seven acute hospitals in North West England. The intervention included serial audit of a bundle of process metrics. An algorithm was developed to identify index ("first") emergency admissions for ARLD (n = 3887). We created a standardised mortality ratio (SMR) to compare relative mortality and regression models to examine risk‐adjusted odds of death. Results: In 2014/2015, three of seven hospitals had an SMR above the upper control limit ("outliers"). Adjusted odds of death for patients admitted to outlier hospitals was higher than non‐outliers (OR 2.13, 95% CI 1.32‐3.44, P = 0.002). Following the QI programme there was a step‐wise reduction in outliers (none in 2017/2018). Odds of death was 67% lower in 2017/2018 compared to 2014/2015 at original outlier hospitals, but unchanged at other hospitals. Process audit performance of outliers was worse than non‐outliers at baseline, but improved after intervention. Conclusions: There was a reduction in unexplained variation in hospital mortality following the QI intervention. This challenges the pessimism that is prevalent for achieving better outcomes for patients with ARLD. Notwithstanding the limitations of an uncontrolled observational study, these data provide hope that co‐ordinated efforts to drive adoption of evidence‐based practice can save lives.